Seismic damage-state classification of prefabricated steel pipe pile–supported wharves using a global lateral stiffness reduction indicator - Jingsong Huang; Qing AI; Lulu Zhang; Yinghui Tian; Shouji Du; Yanping Zhu (Engineering Structures, 2026)

Adaptive decoupling control of key water quality parameters in wastewater treatment processes - Yanping Yao; Xianjun Du; Shengyi Cheng (Journal of Water Process Engineering, 2026)

Insight into the dynamic metabolic transformations and flavor characteristics during solid-state fermentation of Huangjinya dark tea by Eurotium cristatum PW-1 - Yangyu Zhou; Jiuhong Du; Huan Guo; Yanping Wu; Kai Zhong; Yue Xiao; Yina Huang; Hong Gao (Food Research International, 2026)

Corrigendum to “Spatiotemporal prediction of PM2.5 concentration over the Beijing–Tianjin–Hebei region based on forecasting, interpolation, and correction of ERA5 precipitable water vapor” [J. Atmos. Sol. Terr. Phys. 285 (2026), Article 106859] - Xiangshun Meng; Yanping Liu; Yong Wang; Chunhong Liu; Wei Du; Yingliang Wang (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Integrative transcriptomics and metabolomics analyses reveal changes in meat quality and muscle lipid metabolism in sheep supplemented with rumen-protected glucose - Yanping Liang; Jianchuan Shi; Xindong Cheng; Mengyu Feng; Dan Jiao; Xia Du; Kaixi Ji; Shoubin Hu; Qiaoxia Dong; Guo Yang (Meat Science, 2026)

Dual-ion synergistic biopolymer hydrogel: Efficient acid blue 113 adsorption with algal safety - Yanping Jia; Shuo Li; Yaoxin Hu; Jian Zhang; Fei Du; Ruixuan Cai; Lanhe Zhang (Journal of Water Process Engineering, 2026)

Response mechanisms of enhanced biological phosphorus removal systems to microplastics stress - Mingwan Yang; Li Tian; Qihao Li; Guijie Li; Lulu Dai; Anni Du; Liguan Li; Ke Yu; Yanping Mao (Journal of Hazardous Materials, 2026)

Spatiotemporal prediction of PM2.5 concentration over the Beijing–Tianjin–Hebei region based on forecasting, interpolation, and correction of ERA5 precipitable water vapor - Xiangshun Meng; Yanping Liu; Yong Wang; Chunhong Liu; Wei Du; Yingliang Wang (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Synergistic effects of ultrasound-assisted freezing and NADES on the cryostability of surimi gel: Perspective of quality and molecular structure - Yue Chen; Xindi Zeng; Yanping Wang; Xinyan Li; Xin Du; Xiufang Xia (Food Chemistry, 2026)

Molecular dynamics simulation of polyamide based reverse osmosis for boron removal - Yawei Du; Mengru Cui; Jingxin Wei; Yanping Li; Yize Liu; Shizhao Wang; Zhiyong Ji (Desalination, 2026)

Insight into the oxidation mechanism of low-salt Sichuan-style sausages treated with inclusion complexes of tea-polyphenol/β-cyclodextrin/NaCl and electron beam irradiation using machine learning algorithms - Ya Liu; Jiuhong Du; Wenyi Ran; Lihui Huang; Wenyue Yu; Huan Guo; Yue Xiao; Yanping Wu; Kai Zhong; Yina Huang; Hong Gao (Food Chemistry, 2026)

Isolation, characterization, and application of Hanseniaspora uvarum X12 for modulating the flavor and quality of greengage wine through multi-omics and sensory analysis - Hairui Sun; Jiuhong Du; Yanping Wu; Kai Zhong; Yue Xiao; Yina Huang; Hong Gao (Food Bioscience, 2026)

Cytoskeletal control of development and environmental adaptation in plants - Yi Zhang; Jiejie Li; Yun Xiang; Pengwei Wang; Jie Le; Yanping Jing; Ting Wang; Xiangfeng Wang; Lei Zhu; Dong Qian; Guangda Wang; Peiwei Liu; et al. (Science China Life Sciences, 2026)

Quasi-real-time retrieval of ERA5 precipitable water vapor over mainland China - Xiangshun Meng; Yong Wang; Yunlong Zhang; Wei Du; Yanping Liu; Xiao Liu (Advances in Space Research, 2026)

Long-distance lateral migration, accumulation and dissipation of natural gas in the northeastern Ordos Basin, China - Yang Qin; Chiyang Liu; Junfeng Zhao; Faqi He; Wei Zhang; Yanping Ma; Lihua Yang; Deyong Shao; Nan Du; Fuyu Chen (Gondwana Research, 2026)

Multi-omics analyses unveil the molecular mechanism involving flavonoid-mediated color changes of different mango varieties - Yibo Bai; Min Zhu; Bang Du; Yanping Zheng; Aiping Gao; Jianfeng Huang; Yeyuan Chen; Rulin Zhan; Huarui Chen; Xintao Lei; Zhiguo Dang (Food Chemistry, 2026)

Complete genome sequence of a new victorivirus isolated from the phytopathogenic fungus Sclerotinia sclerotiorum - Zhi Zhou; Huang Huang; Du Hai; Jiatao Xie; Jiasen Cheng; Yanping Fu; Daohong Jiang (Archives of Virology, 2026)

Low-dose nano superhydrophobic materials modulate soil health: Dose-dependent trade-offs in microbial communities and plant responses - Linna Du; Xinyi Fang; Xingyu Gong; Yanping Xiao; Fengzhan Tang; Jiacheng Zhou; Mengjie Gu; Ying Su; Yongsheng Song (Journal of Soils and Sediments, 2026)

Chronological and geochemical constraints on the origin and timing of carbonate-cemented sandstones in the Middle Jurassic Zhiluo Formation, northeastern Ordos Basin, China - Yang Qin; Chiyang Liu; Junfeng Zhao; Yanping Ma; Lihua Yang; Nan Du (Marine and Petroleum Geology, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

Phase change nanoemulsions developed by a modified phase inversion temperature method for low-temperature thermal energy storage - Songping Mo; Wenke Cheng; Junhao Chen; Yuxuan Lin; Zicai Pan; Zhi Yang; Lisi Jia; Yanping Du; Ying Chen (International Journal of Refrigeration, 2025)

Synergistic bioaugmentation: Serratia sp. WKD and carboxymethyl cellulose-modified nano-zero-valent iron enhance malachite green decolorization by activated sludge - Linna Du; Xinjiao Dong; Huan Wu; Gang Li; Jiacheng Zhou; Yiqing Wu; Yanping Xiao; Jing Qin; Xiu Wang (Journal of Water Process Engineering, 2025)

Titanium dioxide nanoparticles disturb glucose homeostasis in association with impaired enteroendocrine cell differentiation - Kai Zou; Linna Du; Jing Qin; Jiacheng Zhou; Yanping Xiao; Xixi Song; Hongxia Liu; Xiu Wang (Food and Chemical Toxicology, 2025)

Influence of tin doping on the activity and mechanism of CeO2 catalyst for selective catalytic reduction of NO with NH3 - Jingsong Zhou; Yanping Du; Yuqing Qiao; Fei Zhou; Zhou Liu; Zhibo Xiong; Mengqi Liu; Wei Lu (Journal of Environmental Chemical Engineering, 2025)

Research on PWV fusion based on ERA5 PWV and FY-4A PWV in Chinese mainland - Wei Du; Yong Wang; Xiao Liu; Jing Huang; Yanping Liu; Xiangshun Meng (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Enhancing the quality of dark tea through fermentation with Aspergillus niger: Unveiling aroma and taste characteristics - Maoyun Li; Sicheng Du; Yue Xiao; Yanping Wu; Kai Zhong; Yina Huang; Renyou Gan; Hong Gao (Food Microbiology, 2025)

Critical review on food packaging strategy against spoilage - Lei Liu; Youwei Jiang; Kun Wan; Yanping Wei; Du Tuo; Chuanqin Zhou; Quanguo He; Yimin Tan (Food and Humanity, 2025)

Research on the fusion of PWV over the Beijing-Tianjin-Hebei region based on ERA5 PWV and FY-4A PWV - Wei Du; Yong Wang; Xiangshun Meng; Yanping Liu; Xiao Liu (Advances in Space Research, 2025)

Temporal dynamics of summer phytoplankton communities and their response to environmental changes in the northern Yellow Sea (2011-2020) - Yibo Wang; Zhiliang Liu; Yanping Qi; Yang Chen; Haibo Zhang; Xihan Liu; Du Su (Frontiers in Marine Science, 2025)
Research on phytoplankton distribution and dynamics is crucial for understanding marine ecosystem functions and evaluating their status. The northern Yellow Sea (NYS), a marginal sea of the Pacific Ocean, has experienced significant anthropogenic impacts since the late 20 th century, resulting in an increased nitrogen-to-phosphorus (N/P) ratio and heightened phosphorus limitation. These changes are considered critical factors affecting the phytoplankton community structure in the NYS over recent decades. This study analyzed the temporal dynamics of environmental factors and phytoplankton community structure in the NYS during the summers from 2011 to 2020, aiming to elucidate recent changes in phytoplankton community structure and their driving forces. The results indicated a significant decrease in dissolved inorganic nitrogen (DIN) concentration after 2011, resulting in a decreased N/P ratio, while phosphorus limitation persisted. Temperature, temperature gradient (reflecting stratification intensity) and salinity exhibited upward trends, whereas pH, nitrogen-to-silicon (N/Si) ratio, and chlorophyll- a concentration showed downward trends. The abundances of total phytoplankton, Bacillariophyta, and Dinoflagellata, as well as the Dia/Dino index, fluctuated annually and correlated with temperature, temperature gradient, and nutrient structure. Diversity indices remained stable throughout the study period. The Yellow Sea Cold Water Mass prominently influenced summer phytoplankton community structure, exhibiting lower phytoplankton abundance, Dia/Dino index, and species richness in the cold water mass region, where adaptable species such as Tripos muelleri and Paralia sulcata predominated. Our results emphasized the impact of environmental changes associated with climate change, including rising temperatures, increased salinity, and enhanced stratification, on the phytoplankton community structure in recent years, particularly concerning the dominant species composition and the Dia/Dino index. Therefore, ongoing attention to the effects of climate change on coastal environments and phytoplankton communities is essential.

ENSO modulating tropical cyclone geneses in fall and winter seasons over the South China Sea - Yanping Shi; Lianyi Zhang; Yan Du (Theoretical and Applied Climatology, 2025)

Promotional effect of microwave radiation treatment on the desorption of CO2 from mono-ethanolamine (MEA) solution over FeOOH catalyst - Haoran Zhang; Junge Lv; Zhibo Xiong; Huancong Shi; Jing Jin; Mengqi Liu; Yanping Du; Wei Lu (Journal of Environmental Chemical Engineering, 2024)

Biological invasion is eroding the unique assembly of island herpetofauna worldwide - Weishan Tu; Yuanbao Du; Yoel E. Stuart; Yanxia Li; Yanping Wang; Qingfa Wu; Baocheng Guo; Xuan Liu (Biological Conservation, 2024)

Microplastics distribution, ecological risk and outflows of rivers in the Bohai Rim region of China - A flux model considering small and medium-sized rivers - Xin Hou; Jiayao Li; Hongyu Li; Shuyun Du; Sitong Liu; Shipu Jiao; Fuxin Niu; Jianbo Tu; Yanping Zong; Xiaotong Wang; Xianhua Liu (Science of The Total Environment, 2024)

Quinary metal oxide NiCoMnCeCaOx nanorod as a multifunctional catalyst towards hydrogen production from ethanol steam reforming: Synergistic effect of polymetallic component - Mingzheng Liao; Chunrun Qin; Liujie Xu; Sihan Guo; Chao Wang; Yi Li; Wei Liu; Qingbin Song; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Understandings in surface metal exsolution of NiFeZn ternary alloy/spinel in ethanol steam reforming: The key to hydrogen production - Mingzheng Liao; Wei Liu; Congkang Li; Sihan Guo; Yanyu Chen; Chao Wang; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Response of phytoplankton communities to environmental changes in the Bohai Sea in late summer (2011–2020) - Yibo Wang; Zhiliang Liu; Yanping Qi; Xiao Chen; Yang Chen; Du Su; Xiaobo Yuan; James Klippel-Cooper (Acta Oceanologica Sinica, 2024)

Dynamic relationships and propagation characteristics between meteorological drought and vegetation drought based on a three-dimensional identification algorithm - Fei Wang; Hexin Lai; Zipeng Wang; Ruyi Men; Yanbin Li; Yunzhong Jiang; Kai Feng; Qingqing Tian; Xuefang Du; Yanping Qu (Global and Planetary Change, 2024)

A strategy to assess the use-phase carbon footprint from energy losses in electric vehicle battery - Boran Yang; Chenran Du; Hang Zhang; Xiaoli Ma; Xueling Shen; Dong Wang; Zhanglong Yu; Qian Huang; Danni Gao; Yanping Yin; Yanyan Fang; Ran Xu (Journal of Cleaner Production, 2024)

AKR1C2 genetic variants mediate tobacco carcinogens metabolism involving bladder cancer susceptibility - Yanping Xiao; Yang Shen; Hui Song; Fang Gao; Zhenguang Mao; Qiang Lv; Chao Qin; Lin Yuan; Dongmei Wu; Haiyan Chu; Meilin Wang; Mulong Du; et al. (Archives of Toxicology, 2024)

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

Single-cell and multi-omics analyses highlight cancer-associated fibroblasts-induced immune evasion and epithelial mesenchymal transition for smoking bladder cancer - Jiajin Wu; Fang Gao; Rui Meng; Huiqin Li; Zhenguang Mao; Yanping Xiao; Qiuyi Pu; Mulong Du; Zhengdong Zhang; Qiang Shao; Rui Zheng; Meilin Wang (Toxicology, 2024)

Influence of organic sulfur gas-phase sulfation on the NH3-SCR activity of CeO2 catalyst: The competitive adsorption and conversion of CS2 and COS at a low hydrolysis temperature - Zhibo Xiong; Zhenchang Sun; Jiaxing Liu; Yanping Du; Yafei Zhu; Fei Zhou; Jing Jin; Qiguo Yang; Wei Lu (Fuel, 2024)

Changes of MRGs and ARGs in Acinetobacter sp. SL-1 used for treatment of Cr(VI)-contaminated wastewater with waste molasses as carbon source - Hui Wu; Rongxiao Wang; Yanping Ma; Tian C. Zhang; Yexing Yu; Jirong Lan; Yaguang Du (Science of The Total Environment, 2024)

Identification and characterization of Achromobacter spanius P-9 and elucidation of its deoxynivalenol-degrading potential - Feng Yao; Yaowen Du; Siyi Tian; Guoli Chang; Yanping Zhang; Ruiyu Zhu; Chenggang Cai; Suqin Shao; Ting Zhou (Archives of Microbiology, 2024)

High voltage, toughness and improved interfacial ion deposition through a dual-crosslinked and self-healable hydrogel electrolyte for green zinc-ion batteries - Yanping Yang; Luwei Shi; Yaqi Wu; Zhehua Chen; Xinyuan Zhu; Lijun Du; Youfu Wang (Chemical Engineering Journal, 2024)

Strategies for deoxynivalenol (DON) degradation by microbes from organic fertilizers and influence of the bacterial diversity after DON treatment - Feng Yao; Yaowen Du; Siyi Tian; Guoli Chang; Yanping Zhang; Chenggang Cai; Ruiyu Zhu; Suqin Shao; Ting Zhou (International Biodeterioration & Biodegradation, 2024)

Two-stage method recovery of metals from copper slag: Realize the resource utilization of all components - Lanbin Wang; Yangming Xu; Liang Tian; Yu Chen; Anju Yang; Guixiang Gan; Yanping Ma; Yaguang Du (Minerals Engineering, 2024)

Transfer of antibiotic resistance genes from soil to wheat: Role of host bacteria, impact on seed-derived bacteria, and affecting factors - Yanping Shen; Yibo Liu; Yutong Du; Xu Wang; Jiunian Guan; Xiaohui Jia; Fukai Xu; Ziwei Song; Hongjie Gao; Baiyu Zhang; Ping Guo (Science of The Total Environment, 2023)

Promotional effect of H2O introduction on the NH3-SCR activity of the gas-phase sulfated CeO2 catalyst by organic CS2+COS: Influence of H2O concentration - Jiaxing Liu; Yafei Zhu; Zhenchang Sun; Yanping Du; Zhibo Xiong; Fei Zhou; Jing Jin; Qiguo Yang; Wei Lu (Journal of Environmental Chemical Engineering, 2023)

Effects of supplementary thyme on immunity responses, antioxidant indices, rumen enzymes concentrations and rumen bacteria composition in Hu sheep - Xia Du; Xindong Cheng; Kaixi Ji; Abraham Allan Degen; Yanping Liang; Xiukun Wu; Qiaoxia Dong; Mengyu Feng; Dan Jiao; Haitao Cong; Guo Yang (Animal Feed Science and Technology, 2023)

Co-recovery of Mn and Fe from pyrolusite and copper slag with hydrometallurgy process: Kinetics and leaching mechanisms - Lanbin Wang; Yu Chen; Yangming Xu; Yanping Ma; Yaguang Du (Environmental Science and Pollution Research, 2023)

Detoxification and resource utilization of soda ash chromite ore processing residue by copper slag - Lanbin Wang; Yangming Xu; Yanping Ma; Yu Chen; Anju Yang; Guixiang Gan; Yaguang Du; Yan Sun (Process Safety and Environmental Protection, 2023)

Detection of depression marker ASS1 in urine by gold nanoparticles based dual epitope-peptides imprinted sensor - Hong Wei; Zixia Wang; Yanping Wang; Jing Ma; Yan Chen; Min Guo; Yuanyuan Li; Yongling Du; Fangdi Hu (Analytica Chimica Acta, 2023)

Comprehensive analysis of lncRNA-mRNA regulatory network in Populus associated with xylem development - Na Sun; Yufen Bu; Xinyuan Wu; Xiaocen Ma; Haobo Yang; Liang Du; Xiaojuan Li; Jianwei Xiao; Jinxing Lin; Yanping Jing (Journal of Plant Physiology, 2023)

Effect of dietary Agriophyllum squarrosum on average daily gain, meat quality and muscle fatty acids in growing Tan lambs - Yanping Liang; Dan Jiao; Xia Du; Jianwei Zhou; Abraham Allan Degen; Fu Ran; Guancong Sun; Kaixi Ji; Xiukun Wu; Xindong Cheng; Xiaofei Ma; Chaoju Qian; et al. (Meat Science, 2023)

Production of high affinity monoclonal antibody and development of indirect competitive chemiluminescence enzyme immunoassay for gentamicin residue in animal tissues - Peng Dai; Yan Zhang; Yanping Hong; Jianhua Xiong; Huaying Du; Luying Duan; Dan Wang; Yubo Wang; Weijie Deng; Bruce D. Hammock; Wuying Yang (Food Chemistry, 2023)

Luffa rootstock enhances salt tolerance and improves yield and quality of grafted cucumber plants by reducing sodium transport to the shoot - Zhixin Guo; Yanping Qin; Jingli Lv; Xiaojie Wang; Han Dong; Xiaoxing Dong; Tao Zhang; Nanshan Du; Fengzhi Piao (Environmental Pollution, 2023)

An integrative approach for identification of smoking-related genes involving bladder cancer - Fang Gao; Huiqin Li; Zhenguang Mao; Yanping Xiao; Mulong Du; Shizhi Wang; Rui Zheng; Zhengdong Zhang; Meilin Wang (Archives of Toxicology, 2023)

Host adaptation of codon usage in SARS-CoV-2 from mammals indicates potential natural selection and viral fitness - Yanan Fu; Yanping Huang; Jingjing Rao; Feng Zeng; Ruiping Yang; Huabing Tan; Zhixin Liu; Weixing Du; Long Liu (Archives of Virology, 2022)

Fungal dynamic changes in naturally fermented ‘Kyoho’ grape juice - Wenjuan Zhao; Zhiming Zhang; Yuhong Gao; Xiaozhen Liu; Chaojin Du; Fuxian Ma; Sujie Wang; Wanyuan Shi; Yanping Yang; Ruyou Deng; Hanyao Zhang (Archives of Microbiology, 2022)

Occurrence and impacts of tropical cyclones over the southern South China Sea - Yanping Shi; Yan Du; Zesheng Chen; Wen Zhou (International Journal of Climatology, 2020)
This study investigates the seasonal variation of tropical cyclone (TC) occurrences over the southern South China Sea (SCS) based on the Joint Typhoon Warning Center dataset during 1979–2016. In this region, TCs are most active from October to December (OND), rather than in the active TC season from July to October (JASO) in other western North Pacific (WNP). According to the location of their genesis, the southern SCS TCs are divided into two groups. One consists of TCs generating in the WNP, which are induced by a westward steering flow and move into the southern SCS in OND. The other group contains TCs generated locally in the SCS that move into the southern SCS, which peak in OND due to the positive relative vorticity and high genesis potential index (GPI). In this region, TC genesis is influenced by the El Niño‐Southern Oscillation (ENSO). On an interannual scale, TCs tend to occur in La Niña years due to high GPI. In addition, the mid‐level relative humidity and the low level vorticity play important roles in the contribution of the environmental factors of GPI during ENSO. Both composite analysis and a case study show the impact of TCs on precipitation. TC occurrence is accompanied by heavy rainfall, which is triple the amount of climatological rainfall in OND during 1979–2016, over 15 mm⋅day −1 . Nevertheless, the influence of locally generated TCs, rather than TCs generated in the WNP, contributes to more heavy rainfall in the southern SCS.

Genetic dynamics of earlier maturity group emergence in south-to-north extension of Northeast China soybeans - Mengmeng Fu; Yanping Wang; Haixiang Ren; Weiguang Du; Deliang Wang; Rongjun Bao; Xingyong Yang; Zhongyan Tian; Lianshun Fu; Yanxi Cheng; Jiangshun Su; Bincheng Sun; et al. (Theoretical and Applied Genetics, 2020)

Impact of the quasi-biweekly oscillation on the super typhoon tracks in winter over the western North Pacific - Yanping Shi; Yan Du; Zesheng Chen; Chunzai Wang (Climate Dynamics, 2019)

Genetic variation in the GCKR gene is associated with non-alcoholic fatty liver disease in Chinese people - Zhen Yang; Jie Wen; Xiaoming Tao; Bin Lu; Yanping Du; Mei Wang; Xuanchun Wang; Weiwei Zhang; Wei Gong; Charlotte Ling; Songhua Wu; Renming Hu (Molecular Biology Reports, 2011)

Alteration of integrin-associated protein (CD47) on experimental porcine eperythrozoonosis - Wei Li; Ning Du; Binrui Xu; Weixing Dong; Zhe Qu; Yong Wang; Yanping Sui (Veterinary Research Communications, 2008)

Genomic comparison of Yersinia pestis and Yersinia pseudotuberculosis by combination of suppression subtractive hybridization and DNA microarray - Xiaoyi Wang; Dongsheng Zhou; Long Qin; Erhei Dai; Jianguo Zhang; Yanping Han; Zhaobiao Guo; Yajun Song; Zongmin Du; Jin Wang; Jun Wang; Ruifu Yang (Archives of Microbiology, 2006)